Investigating the association between household exposure to Anopheles stephensi and malaria in Sudan and Ethiopia: A case-control study protocol. - Temesgen Ashine; Yehenew Asmamaw Ebstie; Rayyan Ibrahim; Adrienne Epstein; John Bradley; Mujahid Nouredayem; Mikiyas G Michael; Amani Sidiahmed; Nigatu Negash; Abena Kochora; Jihad Eltaher Sulieman; Alison M Reynolds; et al. (PLoS ONE, 2024)
Background Endemic African malaria vectors are poorly adapted to typical urban ecologies. However, Anopheles stephensi, an urban malaria vector formerly confined to South Asia and the Persian Gulf, was recently detected in Africa and may change the epidemiology of malaria across the continent. Little is known about the public health implications of An. stephensi in Africa. This study is designed to assess the relative importance of household exposure to An. stephensi and endemic malaria vectors for malaria risk in urban Sudan and Ethiopia. Methods Case-control studies will be conducted in 3 urban settings (2 in Sudan, 1 in Ethiopia) to assess the association between presence of An. stephensi in and around households and malaria. Cases, defined as individuals positive for Plasmodium falciparum and/or P. vivax by microscopy/rapid diagnostic test (RDT), and controls, defined as age-matched individuals negative for P. falciparum and/or P. vivax by microscopy/RDT, will be recruited from public health facilities. Both household surveys and entomological surveillance for adult and immature mosquitoes will be conducted at participant homes within 48 hours of enrolment. Adult and immature mosquitoes will be identified by polymerase chain reaction (PCR). Conditional logistic regression will be used to estimate the association between presence of An. stephensi and malaria status, adjusted for co-occurrence of other malaria vectors and participant gender. Conclusions Findings from this study will provide evidence of the relative importance of An. stephensi for malaria burden in urban African settings, shedding light on the need for future intervention planning and policy development.